Review of Vaginitis - Sebastian Faro (Hindawi Limited, 1993)
Adisruption of the dynamic equilibrium of the healthy vagina may have significant sequelae, leading to chronic or serious conditions. Therefore, all cases of vaginitis should be accurately diagnosed and appropriately treated.